Uncovering the anti-NSCLC effects and mechanisms of gypenosides by metabolomics and network pharmacology analysis. (5th December 2021) - Qi, Yan-Shuang; Xie, Jin-Bo; Xie, Peng; Duan, Yu; Ling, Ya-Qin; Gu, Yu-Long; Piao, Xiang-Lan
Abstract: Ethnopharmacological relevance: Lung cancer is the chief reason of cancer death worldwide, and non-small cell lung cancer (NSCLC) make up the majority of lung cancers. Gypenosides are the main active constituents from Gynostemma pentaphyllum . Previous studies showed that they were used to remedy many cancers. The effect of gypenosides on NSCLC has never been studied from the perspective of network pharmacology and metabolomics. The mechanism is still not clear and remains to be explored. Aim of the study: To explore the anti-NSCLC activity and mechanism of gypenosides in A549 cells. Material/methods: Gypenosides of G. pentaphyllum were detected by HPLC-MS. The cytotoxicity was detected by MTT assay. The migration, cell cycle and apoptosis of gypenosides were studied by wound healing assay, JC-1 assay and flow cytometry. The mechanism of gypenosides on NSCLC was studied by metabolomics and network pharmacology. Some key proteins and pathways were further confirmed by Western blot. Results: Eleven gypenosides were detected by HPLC-MS. Gypenosides could suppress the proliferation of A549 cells, inhibit the migration of A549 cells, induce apoptosis and arrest cell cycle in G0/G1 phase. Metabolomics and network pharmacology approach revealed that gypenosides might affect 17 metabolite related proteins by acting on 9 candidate targets (STAT3, VEGFA, EGFR, MMP9, IL2, TYMS, FGF2, HPSE, LGALS3), thus resulting in the changes of two metabolites (uridine 5′-monophosphate, D-4′-Phosphopantothenate) and two metabolic pathways (pyrimidine metabolism; pantothenate and CoA biosynthesis). Western blotting indicated that gypenosides might inhibit A549 cells through MMP9, STAT3 and TYMS to indirectly affect the pathways of pyrimidine metabolism, pantothenate and CoA biosynthesis. Conclusions: This study revealed that metabolomics combined with network pharmacology was conducive to understand the anti-NSCLC mechanism of gypenosides. Graphical abstract: Image 1 Highlights: Effect of gypenosides against A549 cells was analyzed by metabolomics and network pharmacology. Gypenosides affected 9 candidate targets and acted on 17 metabolite-related proteins. Gypenosides might inhibit A549 cells through MMP9, STAT3 and TYMS to indirectly affect 2 metabolites and 2 pathways.